Clinical study of sodium hypochlorite, polymyxin b and limewater effect on MMP-3,-8,-9 in apical periodontitis - Carvalho, Cláudio Antonio Talge [UNESP]; Hasna, Amjad Abu [UNESP]; Carvalho, Alessandra Sverberi [UNESP]; Vilela, Polyana Das Graças Figueiredo [UNESP]; Ramos, Lucas de Paula [UNESP]; Valera, Marcia Carneiro [UNESP]; de Oliveira, Luciane Dias [UNESP] (FapUNIFESP (SciELO), 2020)
This study aimed to evaluate sodium hypochlorite (NaOCl), limewater (LW), and Polymyxin B (PMB) as irrigants over MMP-3, MMP-8 and MMP-9. Thirty-three patients with apical periodontitis of single-rooted teeth were treated according to three-experimental groups (n=11): group-1: 2.5% NaOCl was used as irrigant; group-2: 2.5% NaOCl for the first two files and LW: [0.14% Ca(OH)2] for the last two files; group-3: 2.5% NaOCl for the first two files and PMB for the last two files. The association of Ca(OH)2 and CHX was used as an intracanal medication in all groups. Four root canal samplings (S) were collected: S1) immediately after access cavity; S2) after biomechanical preparation; S3) after EDTA application; and S4) after removal of the intracanal medication. After quantification of MMP-3, MMP-8, and MMP-9, the data were analyzed by Friedman and Kruskal-Wallis tests and completed by Dunn test (5%). Regardless the used irrigant, there was no difference in reducing MMP-3 or MMP-8 (P=0,5273, P=0,7048 respectively). However, in reducing MMP-9 (P=0,0246) the NaOCl group was the most effective followed by NaOCl+LW group and NaOCl+PMB group respectively. The intracanal medication [Ca(OH)2 + CHX] with the NaOCl and NaOCl+LW was effective in reducing MMP-8 (P<0,0001, P=0,0025) and MMP-9 (P=0,0007, P=0,0047) respectively, but not for the group of NaOCl+PMB which was not effective in reducing MMP-8 or MMP-9 (P=0,1718, P=0,1953) respectively. NaOCl and NaOCl+LW were effective in reducing MMP-9 levels, and this effectivity could be improved by the use of the intracanal medication [Ca(OH)2 + CHX] in reducing MMP-8 and MMP-9 levels.
Keywords: Calcium hydroxide; Chlorhexidine; Limewater; Matrix metalloproteinases; Polymyxin B